Illegal Electronic Investments in Trade Robot Missions According to the Criminal Law in Indonesia - Samosir, Gelmok; Danil, Elwi; Yunara, Edi; ., Marlina (KnE Social Sciences, 2024)
Various financial technology companies are currently using standard agreements. With the rise of standard agreements, business actors began to include exoneration clauses to release all forms of responsibility for losses suffered by consumers. One of the companies that has included the exoneration clause is Koinworks in Article 5 of the Koinworks Terms & Conditions. Based on this statement, the authors conducted this research using two problem formulations, namely what are the legal consequences of applying the exoneration clause in standard agreements made by financial technology business actors when viewed from Article 1320 of the Civil Code? And how about preventive legal protection against leakage of consumer data by the negligence of financial technology companies? To be able to answer the formulation of the problem, the authors use normative juridical research methods with a statutory approach. The results of the study show that the legal consequences of applying the exoneration clause in standard agreements made by Financial Technology business actors when viewed from Article 1320 of the Civil Code, it can be concluded that the exoneration clause can be null and void by law. Then, preventive legal protection needs to be carried out by optimizing supervision by the Financial Services Authority, such as taking action against companies that have violated statutory provisions before the occurrence of disputes or problems. Keywords: Legal Protection; Data Leakage; Financial Technology Companies.